The genus Dicksonia (Dicksoniaceae) in the western Pacific - Noben, Sarah; Lehnert, Marcus (Phytotaxa, 2013)
A revision of Dicksonia (Dicksoniaceae) in the western Pacific led to the recognition of five species. On New Caledonia, we recognize D. munzingeri and D. perriei as new to science, and the previously described D. baudouini and D. thyrsopteroides. Dicksonia baudouini is easily distinguished from the other species on the island by its persistent spreading hairs on petioles and frond axes. Dicksonia thyrsopteroides, D. munzingeri and D. perriei are mainly distinguished by the characteristics of their petioles but also by the extent of hemidimorphism and the persistence of dead fronds at the trunk. Dicksonia brackenridgei from Fiji, Vanuatu and Samoa matches D. thyrsopteroides in most morphological characters (e.g. hemidimorphism, morphology of fertile segments, petiole) but has similarities to D. baudouini (stalked pinnae, scabrous petioles and axes) as well.